2009
DOI: 10.5694/j.1326-5377.2009.tb02475.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical morbidity and severity of depression in a large primary care sample of older Australians: the DEPS‐GP project

Abstract: Objectives: To estimate the prevalence of depression among older Australians with common medical morbidities, and to determine the association between poor physical health and depression in this age group. Design: Cross‐sectional, postal questionnaire survey. Setting and participants: 20 183 community‐dwelling adults aged 60 years and over, under the care of 383 general practitioners participating in the Depression and Early Prevention of Suicide in General Practice (DEPS‐GP) project (conducted between 2005 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
5
21
0
Order By: Relevance
“…These baseline findings suggest however that intervening with this group is not going to be easy because of their age and associated co-morbidities, with almost half having three or more conditions. Participants were also more than twice as likely to report suffering from depression, compared to those in the 2007 National Survey of Mental Health and Wellbeing [31,32]. This is consistent with the finding that depression is a common co-morbidity with chronic disease conditions or multiple lifestyle risk factors [32,33].…”
Section: Discussionsupporting
confidence: 72%
“…These baseline findings suggest however that intervening with this group is not going to be easy because of their age and associated co-morbidities, with almost half having three or more conditions. Participants were also more than twice as likely to report suffering from depression, compared to those in the 2007 National Survey of Mental Health and Wellbeing [31,32]. This is consistent with the finding that depression is a common co-morbidity with chronic disease conditions or multiple lifestyle risk factors [32,33].…”
Section: Discussionsupporting
confidence: 72%
“…In line with previous literature (e.g., [1, 2, 59]) we hypothesize that the number of illnesses experienced by older adults will be associated with increased depressive symptoms. Also in accordance with prior findings [13, 14] we hypothesize that the proportion of patients who report clinically significant depressive symptoms and at least moderate pain will be higher amongst those with multi-morbidity than those without.…”
Section: Introductionsupporting
confidence: 85%
“…Estimates of multi-morbidity indicate that over 75% of adults older than 75 years presenting to primary care services have two or more chronic illnesses [3]. There is a considerable literature that confirms that the presence of multi-morbidity is associated with increased depressive symptoms in older adults (e.g., [1, 2, 59]). Although relatively few studies have investigated the relationship between multi-morbidity and diagnosed depressive disorders, the research is consistent in indicating that multi-morbidity is associated with a greater risk of a depressive disorder (e.g., [10, 11]).…”
Section: Introductionmentioning
confidence: 99%
“…The Western Australian Centre for Health and Ageing have access to large databases of potential participants from previous studies (DEPS-GP, [33] n = 4305 and HIMS, [34] n ≈ 7500) and these will be utilized to aid recruitment. Participants from these studies who have indicated that they would be happy to have future contact with the Centre will be invited to participate.…”
Section: Methodsmentioning
confidence: 99%